The Effectiveness of the Good Behavior Game on Students' Academic Engagement in Online-Based Learning - Mohammed Al-Hammouri; Jehad A. Rababah (Online Learning)
Online learning has become a dominant form of education, particularly accelerated by the COVID-19 pandemic, providing flexibility but also posing challenges like reduced collaboration, limited student-faculty interactions, and decreased engagement. These issues are compounded for nursing students, whose curriculum emphasizes practical and communication skills. Therefore, there is a pressing need for strategies to enhance online engagement, especially in disciplines where skill development is crucial. This study aims to investigate the effectiveness of the Good Behavior Game (GBG), a behavioral strategy rooted in applied behavioral analysis, in promoting academically relevant behavior among nursing students engaged in online learning, focusing on participation quantity and quality as indicators of engagement. Using a pre-test, post-test design, 95 nursing students from a public university in Jordan were divided into groups exposed to different GBG conditions. Data on participation were collected over 11 weeks, and statistical analyses revealed a significant positive impact of the GBG on student engagement. Combining quality and quantity contingencies in one condition produced the most significant improvement, suggesting the GBG's adaptability and potential as a comprehensive engagement strategy in various disciplines. This research highlights the GBG's potential as a valuable tool for enhancing online education, addressing its limitations by fostering higher student participation and improved engagement quality. Further exploration of its applicability in diverse educational settings and its long-term impact on student outcomes is recommended, solidifying its place as an effective strategy in the evolving education landscape, especially for disciplines like nursing.